Rods progressively escape saturation to drive visual responses in daylight conditions. Issue 1 (December 2017) - Tikidji-Hamburyan, Alexandra; Reinhard, Katja; Storchi, Riccardo; Dietter, Johannes; Seitter, Hartwig; Davis, Katherine; Idrees, Saad; Mutter, Marion; Walmsley, Lauren; Bedford, Robert; Ueffing, Marius; Ala-Laurila, Petri; et al.
Abstract Rod and cone photoreceptors support vision across large light intensity ranges. Rods, active under dim illumination, are thought to saturate at higher (photopic) irradiances. The extent of rod saturation is not well defined; some studies report rod activity well into the photopic range. Using electrophysiological recordings from retina and dorsal lateral geniculate nucleus of cone-deficient and visually intact mice, we describe stimulus and physiological factors that influence photopic rod-driven responses. We find that rod contrast sensitivity is initially strongly reduced at high irradiances, but progressively recovers to allow responses to moderate contrast stimuli. Surprisingly, rods recover faster at higher light levels. A model of rod phototransduction suggests that phototransduction gain adjustments and bleaching adaptation underlie rod recovery. Consistently, exogenous chromophore reduces rod responses at bright background. Thus, bleaching adaptation renders mouse rods responsive to modest contrast at any irradiance. Paradoxically, raising irradiance across the photopic range increases the robustness of rod responses. Rod photoreceptors are thought to be saturated under bright light. Here, the authors describe the physiological parameters that mediate response saturation of rod photoreceptors in mouse retina, and show that rods can drive visual responses in photopic conditions.